Effect of Pinching and Growth Regulators on Growth, Herbage Yield, Essential Oil Content and Oil Yield of Patchouli (Pogostemon patchouli Pellet.) - Asangi, Honnappa; Vasundhara, M (Journal of Horticultural Sciences, 2013)
An experiment was conducted to study the effect of growth regulators on plant growth, herbage yield, essential oil content and oil yield in patchouli (Pogostemon patchouli Pellet.) variety Cim-shreshta, at University of Agricultural Sciences (UAS), GKVK, Bangalore, during 2011-12. Results indicated that fresh and shade-dried herbage and essential oil yield was influenced significantly by growth regulators. It is concluded that pinching at 45 days after transplanting, followed by foliar application of benzyl adenine (300ppm), and, subsequent sprays at each harvest was more effective in increasing the yield compared to Control.